PLASTIC AND RECONSTRUCTIVE MICROSURGERY IN TREATMENT OF PATIENTS WITH PATHOLOGY OF LARGE JOINTS OF EXTREMITIES - Kutyanov, D. I.; Rodomanova, L. A.; Kochish, A. Y. (Travmatologii͡a︡ i ortopedii͡a︡ Rossii, 2012)
Objective: this study aimed to develop approaches to the use of plastic and reconstructive microsurgery in the treatment of patients with pathology of the large joints of extremities. Material and methods. We have studied the results of surgical treatment of 253 patients with injures and diseases of large joints of extremities. All the patients were treated in Russian Scientific-Research Institute of Traumatology and Orthopedics n.a. R.R.Vreden (Saint-Petersburg, Russia) within the period from 2000 to 2011. All the patients had pedicled flap transfer (65,7%) or free tissue transfer (34,3%). 105 patients (41,5%) had additionally various orthopedic operations on joints: primary or revision total arthroplasty, resections of bony tumors and total knee arthroplasty, arthrodesis and internal fixation. Results and conclusions. Microsurgical operations in patients with pathology of large joints of extremities mainly aimed to correct various pathological changes of tissues located in this particular area. In cases of scarry deformations and defects of tissues located in the area of joint microsurgical technologies increase the opportunities for fulfilling total arthroplasty and improve its results as well as results of other orthopedic operations. At the same time microsurgical technologies may be used as preparative operations, single-step maneuvers and operations fulfilled in case of development of local infectious complications.